Climate as an area of strategic intervention in urban development - Plac, Klaudia (Klimat jako obszar interwencji strategicznej w rozwoju miast, 2020)
EU policies currently place significant emphasis on the commitment to ensure climate neutrality. A substantial role in these efforts is to be played by cities and local communities. This paper seeks to fill the gap in the research on the strategic commitment in Polish cities regarding the climate issue. This study has two purposes. It aims to highlight the key fields of local authorities’ climate commitment and also ascertain the extent to which climate is approached as an area of strategic intervention in major Polish cities. The research shows that the matter of climate is viewed in a very narrow sense, with the local authorities’ commitment usually being dedicated to a few areas of intervention. The analysis points to three generations of strategic documents and shows that cities are more likely to address climate issues if they are significantly exposed to climate and climate-induced risks and extreme weather events. It is evident that urban development strategies in Polish cities follow EU policies and their commitment rarely surpass the scope of intervention detailed in these policies or mainstream concepts of urban governance and urban planning
Biblioteka Regionalisty, 2020, Nr 20, s. 109-123
Keywords: development policy; city development strategy; urban climate and bioclimate; European Union Climate and Energy Policy; climate action; polityka rozwoju; strategia rozwoju miasta; klimat i bioklimat miasta; polityka klimatyczno-energetyczna Unii Europejskiej; działania na rzecz klimatu